Quality use of an unlicensed medicine and off label use of a medicine - Vasilka Nicha; Maja Simonoska Crcarevska; Marija Glavas Dodov; Renata Slaveska Raichki (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2014)
This paper gives an overview of the concept and process of quality use of unlicensed medicines and off label use of medicines, with special attention on the professional roles and responsibilities of prescribers and pharmacists. It also focuses on the policy requirements, sets of guidelines, recommendations, best practices, and other aspects addressed under this topic that represent the state of update knowledge. As a complex and specific issue, the use of an unlicensed medicine and off label prescribed medicine in different health care levels is of particular importance for the healthcare settings in the Republic of Macedonia since, the existing regulatory structure requires adoption and development of a comprehensive strategy relating to this topic in the near future with an aim of encouraging and supporting the development and maintenance of a sound health system with high standards of medication-use policies.